Thermodynamic Evaluation of Phase Equilibria in the GdCl3-MgCl2 Binary System - Wang, Yu; Li, Shaobo; Shao, Guoquan (Asian Journal of Chemistry, 2012)
Experimental data for the GdCl3-MgCl2 binary system were subjected to a critical thermodynamic evaluation using the CALPHAD approach. The modified quasi-chemical model were defined in order to describe the Gibbs energies of the liquid phases and the model parameters were optimized from the experimental phase diagram data. The phase diagram and enthalpies of mixing of the GdCl3-MgCl2 system were calculated. Good agreement between the present calculations and the experimental data were obtained.